N-Heterocyclic Germylenes: Structural Characterisation of Some Heavy Analogues of the Ubiquitous N-Heterocyclic Carbenes - Christopher A. Dodds; Alan R. Kennedy; Mark D. Spicer (Heteroatom Chemistry)
The X-ray crystal structures of three N-heterocyclic germylenes (NHGes) have been elucidated including the previously unknown 1,3-bis(2,6-dimethylphenyl)diazagermol-2-ylidene (1). In addition, the X-ray crystal structures of the previously synthesised 1,3-bis(2,4,6-trimethylphenyl)diazagermol-2-ylidene (2) and 1,3-bis(2,6-diisopropylphenyl)diazagermol-2-ylidene (3) are also reported. The discrete molecular structures of compounds 1 to 3 are comparable, with Ge-N bond lengths in the range 1.835-1.875 Å, while the N-Ge-N bond angles range between 83.6 and 85.2°. Compound 2 was compared to the analogous N-heterocyclic carbene species, 1,3-bis(2,4,6-trimethylphenyl)imidazol-2-ylidene (IMes). The major geometrical difference observed, as expected, was the bond angle around the divalent group 14 atom. The N-Ge-N bond angle was 83.6° for compound 2 versus the N-C-N bond angle of 101.4° for IMes. The Sn equivalent of (1), 1,3-bis(2,6-dimethylphenyl)diazastannol-2-ylidene (4), has also been synthesised and its crystal structure is reported here. In order to test their suitability as ligands, compounds 1 to 3 were reacted with a wide range of transition metal complexes. No NHGes containing metal complexes were observed. In all cases the NHGe either degraded or gave no reaction.